The Risks of the would be Modernization of the Country: Sociologists-Riskologists are Required - S. A. Kravchenko (Vestnik MGIMO-Universiteta)
In the article the potential risks are discussed in connection with the programme of modernization put forward by the President of Russia D. A. Medvedev. The author argues that modern risk challenges are mainly due to the ambivalence of the process of innovations taking place in the development of science and technologists: their results are not only expected brining the wealth to people but some of them contain unanticipated consequences with new dangers. The problem of innovative approaches to the national security is analyzed in connection with new possibilities of risk management. The author also states that it is possible to overcome these risk challenges only developing creative humanistic thinking and conducting the preparation of specialists that are sociologists-riskologists and risk-managers. Кравченко С. А. 1.